PENGARUH MEDIA PEMBELAJARAN AUGMENTED REALITY BERBASIS KARTU PADA MATA PELAJARAN IPAS TERHADAP HASIL BELAJAR SISWA KELAS III SD NEGERI 69 BANDA ACEH - Putri, Julita; Syarfuni; Mahmud, Teuku (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether the use of Augmented Reality learning media in the IPAS subject can improve the learning outcomes of third-grade elementary school students. This research employed a quantitative approach using an experimental method with a one group pretest-posttest design. The research subjects were all third-grade students of SD Negeri 69 Banda Aceh. Data were collected through pretest and posttest. The results of the normality test using the Shapiro-Wilk test showed that the significance value for the pretest data was 0.088 and for the posttest data was 0.099. Since both significance values were greater than 0.05, it can be concluded that the data were normally distributed and suitable for further analysis. The results of the Paired Samples Test used to examine the differences between pretest and posttest scores showed a significance value of 0.000 (≤ 0.05) with an average improvement of 25.00000. These results indicate that the use of Augmented Reality learning media has a positive effect on improving students learning outcomes in the IPAS subject. The conclusion of this study is that Augmented Reality learning media in the IPAS subject are effective in improving students learning outcomes on the topic of natural and artificial features in the local area.